Large‐Scale O+ Depletions Observed by ICON in the Post‐Midnight Topside Ionosphere: Data/Model Comparison. Issue 7 (9th April 2021) - Huba, J. D.; Heelis, R.; Maute, A.
Abstract: The Ion Velocity Meter instrument on the Ionospheric Connection Explorer (ICON) satellite measured large depletions in the O+ density (but not H+) in the post‐midnight topside ionosphere on December 23, 2019. This phenomenon has been observed previously but has yet to be explained. The authors provide for the first time a physical explanation for this observation based on a simulation study using the first‐principles, ionosphere/plasmasphere code SAMI3 (Sami3 is also a model of the ionosphere) with neutral atmosphere inputs (neutral wind, density, and temperature) from the whole atmosphere model Whole Atmosphere Community Climate Model with thermosphere and ionosphere extension (WACCM‐X). The physical processes responsible for these observations are (1) the nighttime O+/H+ transition altitude is below the ICON orbit and (2) a prolonged downward E × B drift in the post‐midnight/pre‐sunrise time sector. Interestingly, the authors also find that equatorial plasma bubbles develop in the African and Pacific sectors. Plain Language Summary: The NASA Ionosphere Connection Explorer satellite, successfully launched on October 11, 2019, is designed to investigate changes in the Earth's ionosphere, the transition region from the earth's atmosphere to outer space. One of the instruments on the satellite is the Ion Velocity Meter (IVM) which measures the in situ plasma velocity, temperature, and density. Recently, a surprising finding with the IVM is the development of large depletions in the O+ density after midnight that persist till dawn. Interestingly, the H+ density is not depleted during this time and remains relatively uniform. We were able to reproduce this result using the ionosphere/plasmasphere model SAMI3 with thermospheric inputs from the NCAR whole atmosphere model Whole Atmosphere Community Climate Model with thermosphere and ionosphere extension. Key Points: The Ion Velocity Meter instrument on the Ionospheric Connection Explorer satellite measured depletions in the O+ density after midnight but not in the H+ density Simulations using SAMI3/WACCM‐X were able to capture this behavior The physical processes for these results are associated with the low O+/H+ transition altitude and a prolonged downward E × B drift